Identificação e análise in silico da modulação transcricional de genes de selenoproteínas em Aedes spp - Batista, Taylice Leonel (2022)
Selenium (Se) plays a biological role for many organisms that may include reproduction, immune defense, and disease resistance. A selenoprotein has an amino acid residue containing the element selenium (Se), called selenocysteine (Sec) or 21st amino acid. Selenoproteins are a broad group of proteins identified as misidentified and poorly annotated in databases. These genes are complex due to the ambiguity of the identification codon "UGA", considered a stop codon and selenocysteine signal. SECIS elements are RNA structures essential for selenocysteine incorporation, being used as gene indicators of selenoproteins in bioinformatics. The objective of this research was to evaluate the pre-verbal candidate genes of selenoproteins from Aedes aegypti and Aedes albopictus, in silico, evaluating their modulation during infection by the arboviruses Dengue virus 1 (DENV1) and 2 (DENV2). Search for possible selenoprotein genes in Ae.aegypti and Ae.albopictus, in the NCBI database “National Center for Biotechnology Information” and analysis of the sequences in the Seblastian platform, predictor of SECIS, resulted in the identification in Ae. aegypti from 11 candidate genes for selenoproteins in the mRNA set and 2 in ncRNAs and in Ae. albopictus of 3 possible genes among the set of mRNAs and 3 in ncRNAs. In addition, genes for selenoproteins and genes associated with their biosynthesis machinery were evaluated for their expression at the transcriptional level in two species-derived mosquito strains. All the putative selenoprotein genes already described, as well as the genes associated with the synthesis machinery, were transcribed at different levels. During DENV1 invasion of Ae.aegypti Aag2 cells, there was a transcriptional increase in the Gawky gene, a candidate gene for selenoprotein, and a transcriptional increase in the Sergef gene, a gene for the selenoprotein synthesis machinery. DENV1 infection in Ae. albopictus did not consider the transcriptional modulation of genes. Aag2 cells, during DENV2 infection, significantly decreased transcription of the SelenoK gene commonly found in arthropods, Eif1ax, Kcnt2 and Tigd6, candidate genes, Pstk, Sars1 and Sbp2 genes, machinery genes, and increased transcription of SelenoH, also found in most arthropods. In C6/36 cells there was a transcriptional decrease of SelenoH induced by DENV2 infection and a transcriptional increase of Sars1 and decrease in the transcription of Secp43, another gene in the machinery. Wolbachia co-infection induced a transcriptional increase of SelenoK in Aag2 cells and decreased transcription of the putative selenoproteins Gawky, Girdin, Ikzf1, Kcnt2, Rip3 and Tigd6 and of the machinery genes Efsec, Sbp2 and Sepsecs. In C6/36 cells, Wolbachia co-infection increased SelenoH transcription and increased transcription of Xpr1, a gene predicted in Ae.albopictus, and Efsec. These data corroborate the importance of Se in the nutrition of mosquitoes and may have an implication in the modulation of the immune system during persistent infection by arboviruses of human interest. In fact, the results of the present work reinforce the need for further studies to refine the selenoprotein search tools.